Awareness of usage the artificial sweeteners in food by different population in North Macedonia - Karakashova Lj., Babanovska-Milenkovska F., Velkoska-Markovska L, Durmishi N (International Journal of Food Technology and Nutrition, 2024)
The artificial sweeteners (AS) are popular low-calorie substances used as sugar substitutes, providing strong sweetening effects without adding sugar and energy to the diet. The most popular AS are aspartame, saccharin, and acesulfame K. The aim of this study is to investigate the awareness and knowledge on the usage and health effects of the artificial sweeteners in food products in North Macedonia. Therefore, an online survey was conducted, distributed through Forms media platform on different age population, completed by 392 participants aged 12 years and above, where 69 % were at the age of 30 - 64 old. According to the obtained results, 6 % of respondents do not know what AS are, while 23 % are partially familiar with them. Moreover, 19 % of the respondents do not know how to recognize the additives on the product declarations at all. On the question if the respondents could list which artificial sweeteners they know, 43 % did not know how to answer, and 28 % gave a partially correct or incorrect answer. Also, 35 % of respondents answered that they use artificial sweeteners in order to reduce the calorie intake. Regarding the risk of consuming large amounts of AS in the diet, 15 % of respondents are not aware, and 36 % are partially aware. The results suggest that it is necessary to develop effective strategies for greater education, information and awareness of consumers, about the usage of AS in their diet, as well as about the advantages and risks of their intake.
Keywords: artificial sweeteners, awareness, usage, food products.